Work Posture Risk Classification Using OWAS QEC and Nordic Body Map: Klasifikasi Risiko Postur Kerja Menggunakan OWAS QEC dan Peta Tubuh Nordic - Pranoto, Wiji; Putra, Boy Isma (Indonesian Journal of Innovation Studies, 2025)
General Background Poor work posture in manual tasks is frequently associated with musculoskeletal complaints and reduced occupational safety. Specific Background Ergonomic assessment tools such as Ovako Work Posture Analysis System, Quick Exposure Check, and Nordic Body Map are commonly applied to evaluate physical workload and body discomfort among workers. Knowledge Gap However, integrated evaluation using multiple assessment methods within the same workplace remains limited, resulting in incomplete risk characterization. Aims This study aims to identify work posture risk levels, determine body parts experiencing discomfort, and propose corrective actions through combined OWAS, QEC, and Nordic Body Map assessments. Results Observational scoring and questionnaire analysis reveal several postures categorized as moderate to high risk, with dominant complaints in the back, shoulders, and lower limbs, indicating the need for immediate ergonomic intervention. Novelty The study provides a comprehensive cross-method comparison that strengthens consistency of risk identification within a single case study. Implications The findings support practical redesign of tasks, tools, and working positions to promote safer and more sustainable work systems in industrial settings. Keywords: Ergonomics, Work Posture, Musculoskeletal Disorders, OWAS, Quick Exposure Check Key Findings Highlights Several tasks classified into urgent corrective category Back and upper limb discomfort most frequently reported Task redesign proposed to reduce physical strain